Effect of Intraluminal Thrombus Asymmetrical Deposition on Abdominal Aortic Aneurysm Growth Rate. (June 2015) - Metaxa, Eleni; Kontopodis, Nikolaos; Tzirakis, Konstantinos; Ioannou, Christos V.; Papaharilaou, Yannis
Purpose: To determine the relationship between asymmetrical intraluminal thrombus (ILT) deposition in abdominal aortic aneurysm (AAA) and growth rate and to explore its biomechanical perspective.Methods: Thirty-four patients with AAA underwent at least 2 computed tomography scans during surveillance. The volumes of the AAA (VAAA ) and thrombus (VILT ) and the maximum thrombus thickness (ILTthick ) were computed. Thrombus distribution was evaluated by introducing the asymmetrical thrombus deposition index (ATDI), with positive and negative values (–1<ATDI<1) associated with anterior and posterior ILT deposition, respectively. Finite element analysis was applied to estimate wall stress. Aneurysms were divided into high and low growth rate groups based on the cohort's median growth rate, and the abovementioned parameters were compared between groups.Results: Most AAAs had asymmetrical anterior thrombus deposition. The high and low growth rate groups did not present significant differences in maximum diameter, VAAA, VILT, or maximum ILTthick . However, the high growth rate group had significantly higher ATDI (p=0.02). The ATDI<0 group (posterior ILT distribution) presented a significantly lower median growth rate compared to that of ATDI≥0 group (anterior or symmetrical ILT deposition; p=0.029). The specificity of an ATDI<0 criterion for identifying AAAs with a growth rate below the cohort median was 89%. The ATDI<0 group had a significantly lower posterior maximum wall stress compared with that of the ATDI≥0 group (p=0.03). Overall peak wall stress did not differ between groups.Conclusion: Posterior thrombus deposition in AAAs is associated with significantly lower growth rate and lower posterior maximum wall stress compared with that of AAAs with anterior thrombus deposition and could potentially indicate a lower rupture risk.